Translation and cross-cultural adaptation of the Brachial Assessment Tool for Brazilian Population (Research, Society and Development, 2022)
Objective: Present the translation and cultural adaptation of the BrAT for the Brazilian population. Methodology: This translation and cross-cultural adaptation study involved ten steps proposed by the International Society of Pharmacoeconomics and Outcomes Research (ISPOR): preparation, forward translation, reconciliation, back-translation, back-translation review, harmonization, cognitive debriefing – which comprised: a Delphi study involving Brazilian physiotherapists that should answer a 7-item form, divided into 3 central axes: questionnaire content, structure and cross-cultural adaptation; and a Pilot study involving patients with BPI that were questioned regarding their comprehension on each question of Brazilian version of BrAT -, review of cognitive debriefing, proofreading and final report. Results: The translation process generated the first Brazilian Portuguese version of BrAT. On cognitive debriefing, ten physiotherapists from the five Brazilian regions provided answers on Delphi study, and a consensus ≥ 80% was achieved in all items, with no amendments proposed. The pilot study involved twenty-one patients with BPI who showed full understanding of the translated version of BrAT and did not suggest any changes. After proofreading the instrument, the final Brazilian version of BrAT (BrAT-Brasil) was developed. Conclusion: BrAT-Brasil version proved to be well adapted to the cultural scenario of the Brazilian population. It exhibited successful results in all stages recommended by the international guideline on translation and cultural adaptation of patient-reported outcome measures.